2008
DOI: 10.1007/s00198-008-0650-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and response to treatment in post-menopausal osteoporosis

Abstract: Optimal vitamin D repletion seems to be necessary to maximize the response to anti-resorbers in terms of both BMD changes and anti-fracture efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 18 publications
6
112
0
7
Order By: Relevance
“…Our study shows that there is low percent agreement between the patients' report of calcium, vitamin D, and multivitamin supplementation and physician documentation of these supplements. This is consistent with previous studies that have documented that it is common for medication lists in an EHR to have inaccuracies, especially with regard to medications that are available over the counter [13,14]. One study showed that 43% of the medications listed in the EHR were inaccurate and more than three times as many over-the-counter drugs than prescription medications were missing from the EHR [13].…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows that there is low percent agreement between the patients' report of calcium, vitamin D, and multivitamin supplementation and physician documentation of these supplements. This is consistent with previous studies that have documented that it is common for medication lists in an EHR to have inaccuracies, especially with regard to medications that are available over the counter [13,14]. One study showed that 43% of the medications listed in the EHR were inaccurate and more than three times as many over-the-counter drugs than prescription medications were missing from the EHR [13].…”
Section: Discussionsupporting
confidence: 89%
“…Reports from other countries indicated serum 25(OH)D levels less than 30-32 ng/mL were associated with poorer BMD responses to bisphosphonates and selective estrogen receptor modulators or with increased fracture incidence during anti-osteoporotic pharmaceutical treatment [25][26][27][28].…”
Section: ) Responsiveness To Antiresorptive Medicationsmentioning
confidence: 99%
“…Vitamin D levels below the optimal range limit dietary absorption of calcium, lead to secondary hyperparathyroidism with loss of skeletal calcium to maintain normocalcemia, contribute to falling risk in the elderly, 29 and blunt the bone mineral density (BMD) response and antifracture efficacy of bisphosphonates. 30 Although currently available data offer no consensus on optimal serum levels of 25-hydroxyvitamin D (the storage form of vitamin D that best reflects vitamin D status), a level of 30 ng/mL (to convert to nmol/L, multiply by 2.496) is generally considered adequate; vitamin D intoxication occurs only when levels are higher than 150 ng/mL. 31 The National Osteoporosis Foundation recommends an optimal calcium intake for both men and women younger than 50 years of 1000 mg/d, with an increase to 1200 mg/d for those 50 years and older.…”
Section: Subtrochanteric Femoral Fracturesmentioning
confidence: 99%